Construction and validation of educational technology to prevent complications in intestinal ostomies / periestomy skin - Yterfania Soares Feitosa; Luis Rafael Leite Sampaio; Juliano Teixeira Moraes; Thereza Maria Magalhães Moreira; Karla Maria Carneiro Rolim; Tays Pires Dantas; Francisca Clarisse de Sousa (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To build and validate an educational booklet for preventing complications in intestinal ostomy and peristomy skin. Methods: Methodological study developed in: 1. Survey of the clinical profile of patients; 2. Integrative review; 3. Construction of technology; 4. Validation of educational material. The Delphi technique was used, with 18 judges with expertise in the field of stomatherapy. For data treatment, the Collective Subject Discourse (CSD), descriptive analysis, Kappa Index (K), binomial test and Content Validity Index (CVI) were used. Results: The agreement rate between judges was higher than 0.61, for K p> 0.05, a proportion of 80% for the binomial test and 80% for the CVI. . The booklet showed an excellent index for K, binomial test and global content validity, becoming validated. Final Considerations: The booklet was validated in appearance and content, being an instrument that can favor communication between professionals and people with ostomies.